THE PRIVATE VISIT – RIGHT OR COMPENSATION - Iulia POPESCU (Challenges of the Knowledge Society)
The connection of the person deprived of his/her liberty with the family is an important aspect to be kept in the prison environment both for him/her and for the family. This connection is accomplished in particular by the right to private visit as provided within the legal regulations. Identifying the origins of the right to private visit and establishing the nature of this private right represent a goal, given that its peculiarity is that although it is regarded as a right, its implementation seems to be closer to the concept of reward. The radiography of the concept „private visit” is trying to identify both the willingness of the legislator that regulated this right, but also the realities from the prisons in terms of concrete realization of this right, considering both the legal provisions and the concrete situations in prisons.